1993
DOI: 10.2134/jeq1993.00472425002200040009x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cattle‐Manure Slurry Application on the Solubility of Cadmium, Copper, and Zinc in a Manured Acidic, Loamy‐Sand Soil

Abstract: The concentrations of Cd, Cu, and Zn were evaluated bimonthly in the soil solution of five acidic loamy‐sand soil plots during an 18‐mo period, before and after application of 25 Mg ha−1 cattle‐manure slurry on top of the plots. pH, Cd, Zn, Cu, and Fe concentrations, electrical conductivity (EC), and dissolved organic carbon (DOC) were monitored in the soil‐solution samples extracted from soil down to 80‐cm depth. Dissolved metal concentrations ranged from 9 × 10−7 to 9 × 10−5 mmol m−3 for Cd, from 0.14 to 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(74 citation statements)
references
References 25 publications
4
68
2
Order By: Relevance
“…The negative coefficients suggested that the extractable Cd was less available to roots when the soil OM and soil pH were high. It is understood that organic matter bound metals are less available to plants (Del Castilho et al, 1993). For EDTA extraction method the first, second, and third variables were Cd · amorphous-Fe, crystal-Fe, and soil pH.…”
Section: Superiority Of the Rhizosphere-based Methods Over Other Extramentioning
confidence: 99%
“…The negative coefficients suggested that the extractable Cd was less available to roots when the soil OM and soil pH were high. It is understood that organic matter bound metals are less available to plants (Del Castilho et al, 1993). For EDTA extraction method the first, second, and third variables were Cd · amorphous-Fe, crystal-Fe, and soil pH.…”
Section: Superiority Of the Rhizosphere-based Methods Over Other Extramentioning
confidence: 99%
“…Thus, a larger fraction of these metals is recovered as free hydrated metal ions. Nevertheless, the association of Cd, Ni and Zn with DOM in soil solution is not insignificant and should not be overlooked (Neal and Sposito, 1986;del Castillo et al, 1993;Naidu and Harter, 1998;Weng et al, 2001b).…”
Section: Tablementioning
confidence: 99%
“…The availability for uptake by plant roots may differ between metals bound in soluble complexes and "free" metals. As organic materials influence the binding of heavy metals in soil and speciation in soil solution (Ram and Verloo 1985;McGrath et al 1988;Lo et al 1992;Del Castillho et al 1993), it may also affect plant uptake (Haghiri 1974;McBride et al 1981). Soil pH is another factor influencing the bioavailability of metals, both in terms of sorption in the soil and speciation in the soil solution.…”
mentioning
confidence: 99%